1998
DOI: 10.1111/j.1469-8137.1998.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Aboriginal landscape burning on the Australian biota

Abstract: One of the most complex and contentious issues in Australian ecology concerns the environmental impact of Aboriginal landscape burning. This issue is not only important for the development of a comprehensive understanding of the dynamics and evolution of the Australian biota, but is central to the formulation of appropriate strategies for the conservation of the nation's biodiversity. Ethnographic evidence leaves little doubt that Aboriginal burning played a central role in the maintenance of the landscapes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
193
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(217 citation statements)
references
References 130 publications
1
193
1
3
Order By: Relevance
“…The first is whether there is indeed a trend toward increasing vegetation density in southeastern Australia, as hypothesized by Flannery (1994). Nevertheless, it is generally accepted that burning was used extensively by Aborigines as a land management tool (Bowman 1998). This is a difficult hypothesis to address quantitatively, and efforts to address it qualitatively (by interpreting the journals of early explorers; e.g., Ryan et al 1995, Benson andRedpath 1997) have been subjective, acrimonious, and inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The first is whether there is indeed a trend toward increasing vegetation density in southeastern Australia, as hypothesized by Flannery (1994). Nevertheless, it is generally accepted that burning was used extensively by Aborigines as a land management tool (Bowman 1998). This is a difficult hypothesis to address quantitatively, and efforts to address it qualitatively (by interpreting the journals of early explorers; e.g., Ryan et al 1995, Benson andRedpath 1997) have been subjective, acrimonious, and inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…In grasslands, plant communities are primarily influenced by a combination of biotic and abiotic factors including fire (Sauer ; Wright & Bailey ; Gibson ; Collins & Gibson ; Noy‐Meir ; Bowman ; Collins & Steinauer ), grazing (Axelrod ; Milchunas et al. ; Vinton & Hartnett ; Vinton et al.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fire by Australian aboriginals and impact on plant and animal diversities has received some attention. The habitat mosaic generated enhanced the survival of certain fauna and flora in the monsoon tropics of Australia (Bowman 1998). The habitat mosaic generated enhanced the survival of certain fauna and flora in the monsoon tropics of Australia (Bowman 1998).…”
mentioning
confidence: 99%
“…How aboriginal human activities impact tropical biodiversity is poorly understood outside of Australia and the tropical Amazon (Phillips et al 1994, Bowman 1998). Zent and Zent (2002) suggested that disturbances caused by the Hoti people of the Venezuelan Amazon might have a considerable impact on the biodiversity of the Magigualida forest.…”
mentioning
confidence: 99%